Changing the High-Risk Behaviors of Injecting Drug Users in Iran: Application Theory of Planned Behavior - Ali Khani Jeihooni; Fatemeh Mohammadkhah; Mostafa Bijani; Pooyan Afzali Harsini (The Scientific World Journal)
Background. Injection risk behavior is a major predictor of HIV infection. The present study was conducted to survey the effect of educational intervention based on the theory of planned behavior on changing high-risk behaviors (the high-risk behaviors of injecting and behaviors of transmitting blood diseases to others) of injecting drug users under the coverage of addiction harm reduction centers. Methods. This study is an experimental research on 120 drug addicts in 2021-2022. Two addiction harm reduction centers in Fasa City, Iran, were chosen randomly (one as the test group and the other as the control group). The data collection tool is made up of two parts. The first part is a questionnaire on demographics. The second part is a questionnaire based on the theory of planned behavior, which was made using information from different sources and studies. The training program was set up based on the pretest results and the theory of planned behavior for the test group. Before and six months after the educational intervention, the experimental and control groups filled out the questionnaire. With a significance level of 0.05, the independent t, chi-square, and paired t statistical tests were used to examine the data using the SPSS 22 program. Results. In the test group, the average age of addicts was 37.42 ± 10.55 years, while in the control group, the average age was 38.36 ± 10.09 years (p=0.244). Six months after the educational intervention, all TPB theory’s constructs (knowledge, attitude, subjective norms and perceived behavioral control, behavioral intention, and behavior of injecting drug users) were higher in the test group than in the control group (p=0.001). Conclusion. The results show the effect of this educational intervention in reducing high-risk behaviors related to injection in injection drug addicts, so it is suggested as a useful method to reduce high-risk injection behaviors in these people.